2015
DOI: 10.1111/pcn.12273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment selections by Japanese and US psychiatrists for major depressive disorder: A case vignette study

Abstract: Aims: A review of the published work on treatments for major depressive disorder suggests that there is an alarming gap between guideline recommendations and actual clinical practices worldwide. The purpose of this study was to compare early-career psychiatrists' selections of treatment for mild to moderate major depression in Japan and the USA. Methods:The authors surveyed 120 early-career psychiatrists from two residency programs in Japan and the USA using web-based questionnaires. In response to two case vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Consequently, pharmacotherapies for psychiatric disorders in Japan differed from those recommended by treatment guidelines in other countries. [9][10][11][12][13][14] For example, although most guidelines recommended antipsychotic monotherapy for schizophrenia, the number of antipsychotics used in Japan was higher than that used in other countries. In addition, the use of benzodiazepines as adjunctive treatment for major depressive disorder, which is not recommended in most guidelines, was higher in Japan than in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, pharmacotherapies for psychiatric disorders in Japan differed from those recommended by treatment guidelines in other countries. [9][10][11][12][13][14] For example, although most guidelines recommended antipsychotic monotherapy for schizophrenia, the number of antipsychotics used in Japan was higher than that used in other countries. In addition, the use of benzodiazepines as adjunctive treatment for major depressive disorder, which is not recommended in most guidelines, was higher in Japan than in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…However, a majority of major depressive disorder patients in Japan are not treated according to guidelines, and many patients are treated with multiple drugs, including long-term use of benzodiazepines. 23 In addition, according to the study comparing the treatment choices for major depressive disorder between Japanese and US psychiatrists, 12 the Japanese psychiatrists favored benzodiazepine monotherapy for the treatment of mild major depressive disorder, whereas the US psychiatrists favored antidepressant monotherapy. Given these situations, this study's findings of a significant increase in the total score for clinical knowledge of the guidelines, including the appropriate use of antidepressants and benzodiazepines, may have a positive influence on the clinical treatment of major depressive disorder in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis examining the impact of guidelines on clinical practice in psychiatry, including psychosis and MDD, Nguyen and colleagues found that CPGs frequently had minimal or insubstantial effects on clinical practice in the context of mental health pharmacotherapy [9]. In Japan, prescribing behaviors that did not follow CPGs have been repeatedly reported in the treatment of schizophrenia and MDD [10][11][12][13][14][15][16]. Taken together, these results suggest that it is not easy for psychiatrists to prescribe according to the CPGs and that additional trials may be needed for the successful implementation of CPGs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, lifestyle and circumstances have changed in recent years, and appropriate LFPs may be increasingly needed in modern Japan. With increasing patients seeking help for mental disorders, a previous study reported that psychiatrists in Japan saw an average of 33 patients per day, length of consultation per patients was 8.3 minutes, and Japanese psychiatrists were more likely to choose pharmacotherapy or active monitoring and less likely to select psychotherapy (Nakagawa et al ., ). Thus, concise evidence‐based LFP can be a potentially good option for mild cases of common mental disorders.…”
Section: Specific Cross‐cultural Considerationsmentioning
confidence: 97%